Sol-Gel Titanium Dioxide Nanoparticles: Preparation and Structural Characterization - Oon Lee Kang; Azizan Ahmad; Usman Ali Rana; Nur Hasyareeda Hassan (Journal of Nanotechnology)
Titanium dioxide (TiO2) nanoparticle was achieved in an alternative sol-gel route, as involved in 1 M acidic solution: HCl-tetrahydrofuran (HCl-THF), HNO3-tetrahydrofuran (HNO3-THF), and ClHNO2-tetrahydrofuran (ClHNO2-THF) solution. Resultant TiO2 nanoparticle was further investigated in a systematic analytical approach. Nanoscale TiO2 structure was observed at a moderate hydrolysis ratio (8≤RH≤16). Particle size range was much narrower in an aprotic HNO3-THF medium, as compared to a differential HCl-THF medium. Biphasic TiO2 structure was detected at a certain hydrolysis ratio (RH≥16). Even so, relative anatase content was rather insignificant in an aprotic HCl-THF medium, as compared to a differential HNO3-THF medium. Tetragonal TiO2 structure was observed in the entire hydrolysis ratio (4≤RH≤32). Interstitial lattice defect was evident in an aprotic HNO3-THF medium but absent in a differential ClHNO2-THF medium.